2003
DOI: 10.1096/fj.03-0009fje
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil C5a receptor and the outcome in a rat model of sepsis

Abstract: Complement fragment 5a (C5a)-C5a receptor (C5aR) signaling plays an essential role in neutrophil innate immunity. Blockade of either the ligand or the receptor improves survival rates in experimental sepsis. In the current study, sepsis was induced in rats by cecal ligation/puncture. Early in sepsis C5aR content on neutrophils significantly dropped, reached the nadir at 24 h after onset of sepsis, and progressively elevated thereafter. Western-blot, RT-PCR, and confocal microscopy analyses revealed that the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 50 publications
3
82
0
Order By: Relevance
“…Previously, changes in C5aR expression levels were associated with a poor prognosis during sepsis, 14,15 which indicated the C5aR expression on neutrophils and the presence of circulating form of C5aR in serum were important markers for sepsis patients. However, the coordinated expression of C5aR and C5L2 and their association with disease progression were not detected in patients with sepsis.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, changes in C5aR expression levels were associated with a poor prognosis during sepsis, 14,15 which indicated the C5aR expression on neutrophils and the presence of circulating form of C5aR in serum were important markers for sepsis patients. However, the coordinated expression of C5aR and C5L2 and their association with disease progression were not detected in patients with sepsis.…”
Section: Discussionmentioning
confidence: 98%
“…Internalization of C5aR (as many other G-coupled receptors) has been described in neutrophils and macrophages in mice and may account for diminished activity observed in these cells. 37,38 Internalization of C5aR by progesterone can also explain the diminished macrophage infiltration observed in LPS plus P-treated mice. This observation is supported by the findings of Timmons and Mahendroo.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that C5a production increased rapidly after colitis to the level comparable to that of controls. As interaction between C5a and C5aR easily leads to internalization of the receptor, 33 the drop of C5a level may be due to this effect. To address this, C5aR expression on the surface of peripheral blood leukocytes at the same time point was detected.…”
Section: Complement Activation In Tnbs-induced Colitismentioning
confidence: 99%